A new method for simultaneous quantification of fosphenytoin, phenytoin and its primary metabolite 5-(4-hydroxyphenyl)-5-phenylhydantoin in whole blood by ultra-performance liquid chromatography-tandem mass spectrometry. (September 2018) - Suzuki, Takayoshi; Ogawa, Tadashi; Ueyama, Jun; Iwai, Masae; Kondo, Fumio; Seno, Hiroshi
Highlights: Fosphenytoin (F-PHT) is an antiepileptic drug for epilepsy and bipolar disorders. F-PHT has the narrow therapeutic index. Forensic practice often requires analysis of drugs and poisons in whole blood. We developed a quantification method for F-PHT and its metabolites by UPLC-MS/MS. This method appears to be suitable for forensic and clinical toxicology. Abstract: A method for simultaneous quantification of fosphenytoin (F-PHT), phenytoin (PHT) and its main metabolite 5-(4-hydroxyphenyl)-5-phenylhydantoin (HPPH) in whole blood was developed and validated using ultra-performance liquid chromatography-tandem mass spectrometry. Whole blood samples were pretreated by liquid–liquid extraction with acetonitrile and methanol. Chromatographic separation was performed using a CORTECS™ UPLC® C18 (2.1 × 50 mm i.d., particle size 1.6 μm) analytical column, and water containing 10 mM ammonium formate and acetonitrile as the mobile phase. Quantification of the analytes was carried out using mass chromatography with each product ion referenced against phenytoin-d10 as an internal standard. Calibration curves exhibited good linear relationships in a range from 0.005 to 50 μg/ml with correlation coefficients exceeding 0.995. The limits of detection were estimated to be 0.002–0.01 μg/ml. The accuracies and precisions were 96.2–104.3% and 0.7–10.7%, respectively. The recovery efficiencies were in the range of 42.4–59.2%. Matrix effects were observed for PHT and HPPH, with signal suppression ranging from −6.6 to –32.2%. Matrix effect for F-PHT (−5.0 to 8.9%) was less than those for PHT and HPPH. All analytes were stable under different storage conditions. This method was successfully applied for the quantification of F-PHT, PHT and HPPH in rat whole blood samples taken after bolus intravenous administration of F-PHT.